2008
DOI: 10.1080/15569520802327005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a ModifiedIn vitroSkin Absorption Method to Study the Epidermal/Dermal Disposition of a Contact Allergen in Human Skin

Abstract: In vitro skin absorption methods exist in Organisation for Economic Co-operation and Development (OECD) guideline form (No. 428) and are used to estimate the degree of systemic penetration of chemicals through skin. More detailed kinetics of permeation through skin compartments are not described well by existing methods. This study was designed to assess the practical feasibility of generating compartmental (stratum corneum/epidermal/dermal) disposition and kinetic data of topically applied chemicals. For chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 6 publications
2
15
0
Order By: Relevance
“…The overall findings of this study are in good agreement with the work by Pendlington et al [26] , who examine the penetration rates of cinnamaldehyde in these same vehicles in vitro with radiolabelling methods. The two methods provide complementary data, the radiolabelling method giving the amount of penetration to the receptor solution, the Raman method giving more details about the penetration into the top layers of the skin and more time points.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The overall findings of this study are in good agreement with the work by Pendlington et al [26] , who examine the penetration rates of cinnamaldehyde in these same vehicles in vitro with radiolabelling methods. The two methods provide complementary data, the radiolabelling method giving the amount of penetration to the receptor solution, the Raman method giving more details about the penetration into the top layers of the skin and more time points.…”
Section: Discussionsupporting
confidence: 82%
“…In practice the Raman signal from each chemical needs to be above a certain working limit of detection, and as more components are added to the mixture, the resolution of each chemical becomes more challenging. Cinnamaldehyde was observed to penetrate at different rates from four different vehicles, the order of which, acetone 1 aqueous ethanol 1 absolute ethanol 1 propylene glycol 1 olive oil, matches a previous study using different methods [26] . Also it was found that the vehicle of preference for the LLNA assay, acetone:olive oil, phase separates on the skin surface with subsequent consequences for adsorption rates into the skin.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…The disposition of volatile organic compounds (VOCs) after dermal application has been studied in the past (Gilpin et al, 2009;Kasting et al, 2007;Pendlington et al, 2008). Acknowledging the fact that consumer products designed for topical applications are usually complex and often non-aqueous systems containing multiple ingredients, researchers attempted to investigate the influence of the formulation on dermal absorption (Reifenrath and Robinson, 1982;Saiyasombati and Kasting, 2003) and evaporation (Nihi et al, 2009;Vuilleumier et al, 1995) for a range of VOCs.…”
Section: Introductionmentioning
confidence: 98%
“…A key element of this work is to improve our current estimates of dermal exposure to ingredients for which we have detailed information on both formulation effects and consumer habits and use patterns. A new experimental approach based on ex vivo human skin has been investigated to determine skin compartmental concentrations and the delivery kinetics of a chemical in vitro (Pendlington et al, 2008). Techniques like this aim to establish a relationship between the exposure on the skin and the chemical bioavailability at the target site assumed to be the epidermis and dermis.…”
Section: Skin Allergymentioning
confidence: 99%